Digital learning using Maktabah Syumilah NU 1.0 software and computer application for Islamic moderation in pesantren - Hamidulloh Ibda; Aji Sofanudin; Moh. Syafi’; Ana Sofiyatul Azizah; Muhamad Arif; Novena Ade Fredyarini Soedjiwo (Institute of Advanced Engineering and Science, 2023)
Digital learning through computer software and applications is rarely applied by pesantren (Islamic boarding schools) in Indonesia. So far, the application commonly used by traditional (salaf) pesantren, modern (khalaf) pesantren, and integrated pesantren is the Maktabah Syamila application. However, in Maktabah Syamila, religious radicalism, false hadiths, and texts allow the killing of innovators. Responding to this, pesantren activists developed digital learning through the application and computer program Maktabah Syumilah NU 1.0 as a comparison to Maktabah Syamila and an alternative to learning in pesantren as a counterradicalism. The research explores digital learning through Maktabah Syumilah NU 1.0 software and computer application to cultivate religious moderation in Temanggung Regency, Central Java, Indonesia. The qualitative research method with case studies on ten traditional pesantren using Maktabah Syumilah NU 1.0. The results show that digital learning through Maktabah Syumilah NU 1.0 is carried out in various activities in and outside the pesantren. The application of Maktabah Syumilah NU 1.0 is used to cultivate Islamic moderation for santri (students of pesantren). The use of Maktabah Syumilah NU 1.0 has an impact on strengthening Islamic moderation in pesantren. This research recommends that the Ministry of Religious Affairs implement Maktabah Syumilah NU 1.0 in all pesantren. Future researchers must explore digital learning more deeply through the latest applications for strengthening Islamic moderation in pesantren.